2021
DOI: 10.1002/bab.2124
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of caffeic acid biotransformation into para‐hydroxybenzoic acid by Candida albicans CI‐24 via gamma irradiation and model‐based optimization

Abstract: Para‐hydroxybenzoic acid (PHBA) has great potential in biological applications due to its putative antiviral activity against SARS‐CoV‐2 and its antimicrobial activity in the face of the radically increasing number of multidrug‐resistant pathogens. This is in addition to its antimutagenic, anti‐inflammatory, antioxidant, hypoglycemic, antiestrogenic, and antiplatelet aggregating activities. In this study, an approximate sixfold increase in the production of PHBA was achieved via biotransformation of caffeic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…19 Response surface methodology (RSM) is one of the most prominent chemometric tools. 20 Employing RSM tools offers multiple merits, encompassing less performed experiments, less consumed chemicals, and less time and effort. This is in addition to generating mathematical models indicating the independent as well as interactive significance of the different variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Response surface methodology (RSM) is one of the most prominent chemometric tools. 20 Employing RSM tools offers multiple merits, encompassing less performed experiments, less consumed chemicals, and less time and effort. This is in addition to generating mathematical models indicating the independent as well as interactive significance of the different variables.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemometric tools have been preferably employed in optimization studies 19 . Response surface methodology (RSM) is one of the most prominent chemometric tools 20 . Employing RSM tools offers multiple merits, encompassing less performed experiments, less consumed chemicals, and less time and effort.…”
Section: Introductionmentioning
confidence: 99%
“…Rutin and gallic acid were also reported in the study of Alia et al (11) on the crude extract of C. violaceae, whereas they also reported the presence of chlorogenic acid and naringin. On the other hand, Piwowarczyk et al Several studies have indicated that many of the identified compounds in our extracts have been isolated from various plants and have a wide range of biological effects, including anti-inflammatory, antioxidant, antimicrobial, antitumor, and others (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 97%
“…Gallic acid is a low molecular weight tri-phenolic molecule that has outstanding anti-inflammatory, antioxidant, antitumor, antidiabetes, antiobesity, antimicrobial, and anti-myocardial ischemia properties (31). p-hydroxybenzoic acid and its derivatives have been reported by Singab et al (33) to have potential antimicrobial, antiviral action against SARS-CoV-2, antimutagenic, anti-inflammatory, antioxidant, hypoglycemic, antiestrogenic, and antiplatelet aggregating activities. This compound can be chemically synthesized or recovered from various plants (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation